Consumer’s Perception and Satisfaction About Household Water Filter at Taman Tunku, Miri Sarawak - TAKA, RAFINA RACHEL; KHAMIDUN, Dr. MOHD HAIRUL BIN KHAMIDUN (Recent Trends in Civil Engineering and Built Environment, 2023)
Water filter has no longer becomes desire but more to necessity. This is because humans need to consume water for daily routine to stay hydrated. This allows the users to choose which water filter that suites with their preferences and also what factors that affects the decision making in the process of buying a new water filter. Therefore, the objectives of this study are to investigate the level of understanding and knowledge of consumers about the household water filter identify the satisfaction level of a consumer once they used the water filter, to evaluate the response level of consumers towards the improvement of water quality using household water filters and to determine the satisfaction level of consumers using household water filters. This study employs a quantitative approach, employing the Chronbach’s Alpha Test and the Chi Square Test to assess the reliability and dependability of its variables. The Cronbach’s Alpha test result for this study is 0.873, indicating that the variables provided are reliable enough, while the Chi Square Test result shows the calculated value for gender and its level of satisfaction is 15.80, for the consumer’s age and level of satisfaction is 55.01, for the consumer’s profession and level of satisfaction is 35.29, and finally for the years settled and the level of satisfaction is 35.29. These variables suggest that the variables have a significant relationship. To summarize, the decision to own a water filter is more likely to be driven by the consumer’s knowledge of the importance of the water filter as well as the benefits that it provides over time, as these consumers have noticed that the water becomes clearer and have more confidence in drinking water directly from the water filter.